2002
DOI: 10.1029/2001gb001421
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal cycles and seasonal variation of isoprene and its oxidation products in the tropical savanna atmosphere

Abstract: [1] Using the proton transfer reaction mass spectrometry (PTR-MS) technique, isoprene and its oxidation products were measured in a productive woodland savanna (Calabozo site, during the wet and dry seasons) and a less productive grassland savanna (La Gran Sabana, Parupa site). The measured protonated masses in the PTR-MS, postulated compounds, and daytime average volume mixing ratios at the Calabozo site during the wet season are: 69 isoprene (1.62 nmol/mol), 71 methyl vinyl ketone + methacrolein (0.98 nmol/m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
19
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 51 publications
5
19
0
Order By: Relevance
“…This overestimate is consistent with findings in other 3D global model studies (Houweling et al, 1998;Granier et al, 2000). Besides too high emissions of the rainforest ecosystem as also suggested by Rinne et al (2002) other factors such as too weak vertical mixing or unknown deposition processes (Holzinger et al, 2002) could contribute to the overestimate. In fact, over Surinam the model predicts a too strong decrease of isoprene with altitude compared to the measurements by Warneke et al (2001) which indicate efficient mixing by shallow convection up to 4 km.…”
Section: Model Performancesupporting
confidence: 81%
See 1 more Smart Citation
“…This overestimate is consistent with findings in other 3D global model studies (Houweling et al, 1998;Granier et al, 2000). Besides too high emissions of the rainforest ecosystem as also suggested by Rinne et al (2002) other factors such as too weak vertical mixing or unknown deposition processes (Holzinger et al, 2002) could contribute to the overestimate. In fact, over Surinam the model predicts a too strong decrease of isoprene with altitude compared to the measurements by Warneke et al (2001) which indicate efficient mixing by shallow convection up to 4 km.…”
Section: Model Performancesupporting
confidence: 81%
“…Hydroxyhydroperoxides from isoprene (ISOOH and MACROOH), which are assumed to form in NO x -bereft environments are explicitly treated in the scheme. These compounds have been tentatively identified over the rainforest in Surinam Warneke et al, 2001) and over the savanna in Venezuela (Holzinger et al, 2002).…”
Section: Chemical Schemesmentioning
confidence: 99%
“…The observed signal on m / z 61, reported as acetic acid (∼6% yield), may result from the production of glycolaldehyde, and m / z 73 and 75, likely corresponding to methylglyoxal and hydroxyacetone. Several ions were observed from isoprene photooxidation, including m / z 113, a dominant ion observed in ambient air [ Holzinger et al , 2005], and m / z 101 (Table 8), which has also been observed by PTR‐MS in ambient air above a tropical rain forest [ Warneke et al , 2001] and a tropical savanna [ Holzinger et al , 2002], and may be the C 5 hydroxycarbonyls reported by Zhao et al [2004] and Baker et al [2005].…”
Section: Resultsmentioning
confidence: 94%
“…For this reason both would result in a different diurnal cycle than observed. Like for isoprene, increasing mixing ratios during daytime are expected for light-triggered sources (Holzinger et al, 2002); temperaturetriggered sources would produce high concentrations in the evenings, when emissions are still strong but vertical mixing is suppressed by the developing nocturnal boundary layer. Biomass burning emissions of CH 3 CN coincide with substantial emissions of CO and a correlation between the two gases can be expected.…”
Section: Resultsmentioning
confidence: 99%